Platelet Contributions to the (Pre)metastatic Tumor Microenvironment - Roweth, Harvey G. (Seminars in Thrombosis and Hemostasis, 2023)
Alongside their conventional roles in thrombosis and hemostasis, platelets have long been associated with nonhemostatic pathologies, including tumor cell metastasis. Numerous mechanistic studies have since demonstrated that the direct binding of platelets to intravascular tumor cells promotes key hallmarks of metastasis, including survival in circulation and tumor cell arrest at secondary sites. However, platelets also interact with nonmalignant cells that make up the stromal and immune compartments within both primary and metastatic tumors. This review will first provide a brief historical perspective on platelet contributions to metastatic disease before discussing the emerging roles that platelets play in creating microenvironments that likely support successful tumor cell metastasis.
Keywords: cancer; platelets; metastasis; pre-metastatic niche